Current Perspectives on Mycobacterium farcinogenes and Mycobacterium senegalense, the Causal Agents of Bovine Farcy - Mohamed E. Hamid (Veterinary Medicine International)
Mycobacterium farcinogenes and M. senegalense are the causal agents of bovine farcy, a chronic, progressive disease of the skin and lymphatics of zebu cattle. The disease, which is prevalent mainly in sub-Saharan Africa, was in earlier times thought to be caused by Nocardia farcinica and can be described as one of the neglected diseases in cattle. Some aspects of the disease have been investigated during the last five decades but the major development had been in the bacteriological, chemotaxonomic, and phylogenetic aspects. Molecular analyses confirmed that M. farcinogenes and M. senegalense fall in a subclade together with M. houstonense and M. fortuitum. This subclade is closely related to the one accommodating M. peregrinum, M. porcinum, M. septicum, M. neworleansense, and M. alvei. DNA probes were designed from 16S-23S rRNA internal transcribed spacer and could be used for the rapid diagnosis of bovine farcy. An ELISA assay has been evaluated for the serodiagnosis of the disease. The zoonotic potentials of M. farcinogenes and M. senegalense are unknown; few studies reported the isolation of M. senegalense and M. farcinogenes from human clinical sources but not from environmental sources or from other domestic or wild animals.